2012
DOI: 10.1111/j.1552-6569.2012.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of FDG Uptake in the Arterial Wall as an Imaging Biomarker of Atherosclerotic Plaques with 18F‐Fluorodeoxyglucose Positron Emission Tomography‐Computed Tomography (FDG‐PET/CT)

Abstract: Background and Purpose From the literature the prevalence of FDG uptake in large artery atherosclerotic plaques shows great heterogeneity. We retrospectively reviewed 100 consecutive patients who underwent FDG-PET/CT imaging of their whole body, to evaluate FDG uptake in the arterial wall. Materials & Methods We retrospectively evaluated 100 whole-body PET-CT scans. The PET co-registered CT images were reviewed with for abnormal 18F-FDG uptake. The mean standard uptake value (SUV) was measured in regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Cardiovascular 18 F-FDG PET detected arterial and myocardial inflammation in several preclinical studies131415 and clinical trials16171819202122. We, therefore, correlated 18 F-FDG and Macroflor uptake in rabbits with atherosclerosis.…”
Section: Discussionmentioning
confidence: 94%
“…Cardiovascular 18 F-FDG PET detected arterial and myocardial inflammation in several preclinical studies131415 and clinical trials16171819202122. We, therefore, correlated 18 F-FDG and Macroflor uptake in rabbits with atherosclerosis.…”
Section: Discussionmentioning
confidence: 94%
“…Pharmacotherapy trials have demonstrated both positive and negative effects on signal uptake in carotid atheroma, 30 yet there are further successful trials that have used PET/CT as an imaging biomarker in other arterial beds, for example the aorta and iliac vessels, 31 and it is likely to be that such imaging has distinct advantages as an outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…Ультразвуковой метод обладает высоким разрешением, но исследование грудной аорты требует транспищеводно-го доступа [57,59]. ПЭТ проявляет высокую чувствитель-ность при выявлении очагов воспаления сосудистой стен-ки, однако накопление 18F-фтордезоксиглюкозы в стен-ке сосудов не является специфичным для васкулита и дифференциация результатов ПЭТ с атеросклеротиче-ским поражением [60] может становиться непростой за-дачей.…”
Section: Discussionunclassified